Young People and the Fragmentation of Religious Authority: Study of Youth Movements and the Spirit of Islamic Da’wah in Indonesia - Kholidi, Iqbal; Umam, Fawaizul; Wazis, Kun; Jali, Hasan (JURNAL AT-TURAS, 2024)
The rise of religious authority among young people in Indonesia has become increasingly prominent, particularly with the proliferation of da'wah movements across diverse domains. This trend is evidenced by the surge of Islamic activism initiated by Indonesian youth. This study seeks to explore the methods through which young individuals assert and cultivate their religious influence and the ethos of Islamic resurgence within the public sphere. Conducting field research in Probolinggo, Bondowoso, and Lumajang, supplemented by netnography examining youth social behaviors and existing literature, this paper unveils several key findings. Firstly, young Indonesians establish da'wah communities in various formats, such as majelis shalawat, sarwah, and majlas. Secondly, they exhibit a preference for popular shalawat music in the Indonesian language. Thirdly, there is a widespread utilization of social media platforms as a means of disseminating their da'wah messages. Lastly, young Muslims manifest their religious authority through fashionable and contemporary styles of dress.